2022
DOI: 10.1155/2022/2517463
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-424-5p Alleviates Isoflurane Anesthesia-Induced Neurotoxicity in Human Embryonic Stem Cell-Derived Neurons by Targeting FASN

Abstract: Isoflurane (ISO) is a type of anesthetic that might cause neurotoxicity in children. Although miR-424-5p is considerably downregulated in ISO-treated rat brain samples, its physiological role in ISO-induced neuronal injury in human embryonic stem cell-derived neurons remains unknown (hESC-derived neurons). miR-424-5p expression and fatty acid synthase (FASN) in ISO-treated hESC-derived neurons were tested via qRT-PCR. The amount of protein for Bax, Cleaved-caspase-8, Bcl-2, and FASN was investigated through we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%